Caracterização fitoquímica do extrato de Pilosocereus gounellei A. Weber ex K. Schum. Bly. ex Rowl. (Cactaceae) e avaliação de suas atividades antioxidante e microbiológica - Maciel, Jéssica Karina da Silva (2016)
The species Pilosocereus gounellei A. Weber ex K. Schum. Byl. ex Rowl (Cactaceae), popularly known as “xique-xique” is endemic in Brazilian semiarid with habitat from Maranhão to Bahia. It has been reported that the roots marerated is used in popular medicine to treat urinary diseases and prostate inflammation, and the cladodes macerated has been used to treat gastritis. The phytochemical study of P. gounellei provided the isolation and identification of nine compounds, being three steroids, ßsitosterol, a mixture of ß-sitosterol with stigmasterol and a mixture of ß-sitosterol and stigmasterol glucosides; three flavonoids, pinostrobin, quercetin and kaempferol; one porphyrin compound, pheophytin a; besides two alkamides, trans-feruloyl thiramine and 7'-ethoxytransferyleryramine (mariannein), which is being described for the first time in the literature. The structural characterization of the substances was performed by spectroscopic methods such as uni and bi -dimensional 1H and 13C NMR. The antioxidant activity analysis of methanolic fraction, cladodes, roots, flowers and fruits extracts showed that the fruit extract possess great antioxidant potential, being a candidate for nutraceutical product. The antimicrobial screening revealed that all the samples of P. gounellei, except for the fruits extract and methanol fraction, have a moderate activity against E. colli. The validated analytical method, using HPLC-ELSD, led to quantify the ß-sitosterol in cladodes extract (0.38 ± 0.023 mg ß-sitosterol / g cladodes extract) and contributed to the quality control of raw-material plant. The present study suggests that P. gounellei has great potential to become a nutraceutical product with excellent activity against free radicals.